1993
DOI: 10.1111/j.1439-0434.1993.tb01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Virus Resistance Induced with Mannan Sulphates in Hypersensitive Host Plants

Abstract: Mannan sulphates (MS), obtained by sulphatation of extracellular linear mannan (LM) from Rhodotorula rubra, induced resistance to tobacco mosaic virus (TMV) in hypersensitive plants, retained in isolated protoplasts. MS‐induced resistance in tobacco is accompanied by a marked increase of lytic processes in cells and a decrease of total (acidic and alkaline) protein content. In addition to this, new protein components, including PR‐proteins and antiviral substances, of the inhibitor of virus replication (IVR) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…The optimum dose of UV irradiation used by Mercier et al was 2 20 x 10^ erg/cmŜ emi-synthetic elicitors Semi-synthetic elicitors are chemically modified biotic compounds. For example, the natural linear mannan from Rhodotorula rubra (Kovalenko et al, 1993) has no elicitor activity, but sulphated forms have antiviral activity which appears to work via an induction of host defence responses such as PR proteins. Unfortunately, these mannan sulphates are also phytotoxic and therefore have little practical potential.…”
Section: Abiotic Elicitorsmentioning
confidence: 99%
“…The optimum dose of UV irradiation used by Mercier et al was 2 20 x 10^ erg/cmŜ emi-synthetic elicitors Semi-synthetic elicitors are chemically modified biotic compounds. For example, the natural linear mannan from Rhodotorula rubra (Kovalenko et al, 1993) has no elicitor activity, but sulphated forms have antiviral activity which appears to work via an induction of host defence responses such as PR proteins. Unfortunately, these mannan sulphates are also phytotoxic and therefore have little practical potential.…”
Section: Abiotic Elicitorsmentioning
confidence: 99%
“…Despite the popularity of this charge mediated mode of action, there is strong evidence that it may not be the only antiviral effect that polysaccharides exert. In the past 8 years several studies have found polysaccharides to elicit plant defences and induce systemic acquired resistance (SAR) to crop pathogens Mercier et al, 2001;Kovalenko et al, 1993). Some algal polysaccharides, for example krninarin, are capable of mimicking natural elicitors, which upon recognition at the surface of the host cell stimulate the expression of plant defence genes (Mercier et al, 2001).…”
mentioning
confidence: 99%
“…These effects appear to be widespread, having been induced in assays using wheat, soyabean, alfalfa and tobacco. To date most studies have focused on testing resistance to the two most costiy crop pathogens, fungi and viruses Mercier et al, 2001;Kovalenko et al, 1993).…”
mentioning
confidence: 99%
“…Для вивчення клітинної локалізації речовин, що мають антивірусну і гемаглютинуючу актив ності, ФБС-екстракти з ураженого (7 діб після інокуляції ВТМ) та здорового листя розділяли на розчинну (105000 g -супернатант), мікросомнорибосомну (105000 g -осад) та ядерно-хлоропластно-мітохондріальну фракції (17000 g -осад) за допомогою диференційного центрифугування, як описано в роботі [11]. Солюбілізацію структурно зв'язаних компонентів з органел здійснювали 1 %м розчином тритону Х-100 в 0,1 М ФБС, рН 7,4.…”
Section: телегеєва а м кириченко 2003unclassified